Scale armor on the North American frontier: Lessons from the John G. Bourke armor. (August 2015) - Bleed, Peter; Long, Lindsay; Long, Jessica; Roberg, Madeleine; Killick, David
Abstract : In 1870, as he was starting his career as a frontier army officer and anthropologist, John Bourke collected a gorget composed of iron scales and the story that it was a relic of early Spanish exploration of the Plains. This paper describes the Bourke armor and assesses its manufacture, history, and cultural context. The origins of the armor remain uncertain, but it seems unlikely that it arrived during initial Spanish explorations of the Plains. The armor probably dates from before the early nineteenth century.